1987
DOI: 10.1111/j.1751-0813.1987.tb09638.x
|View full text |Cite
|
Sign up to set email alerts
|

Virus and virus‐like particles in the faeces of cats with and without diarrhoea

Abstract: Negative staining electron microscopy was used to identify viruses in 166 normal and 62 diarrhoeal faecal samples from 208 cats admitted to an animal shelter during a 16-month period (March 1984 to June 1985). On the basis of size and shape 7 distinct viral types were detected: 24 nm parvovirus-like particles, 30 nm astrovirus, 30 nm picornavirus-like particles, reovirus, rotavirus, coronavirus and a 75 nm "togavirus-like" particle. The incidence of these particles in the 208 cats was 11%, 7%, 6%, 0.4%, 5%, 1%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 28 publications
2
59
2
1
Order By: Relevance
“…Several reports showed that astroviruses are present worldwide and represent the second most important cause of gastroenteritis in children, after rotaviruses (Herrmann et al, 1991;Matsui et al, 2001;Moser and Schultz-Cherry 2005;De Benedictis et al, 2011). Astroviruses have also been identified in several animal species, such as cats, swine, sheep, minks, cheetahs, sea lions, bottlenose dolphins, red deer, dogs, rodents and bats (Woode and Bridger, 1978;Snodgrass et al, 1979;Gray et al, 1980;Williams, 1980;Tzipori et al, 1981;Bridger et al, 1984;Shirai et al, 1985;Woode et al, 1985;Harbour et al, 1987;Marshall et al, 1987;Vieler and Herbst, 1995;Englund et al, 2002;Lukashov and Goudsmit, 2002;Zhu et al, 2009;Blomström et al, 2010;Chu et al, 2010;Reuter et al, 2011;Tse et al, 2011). Recently, new astroviruses (MBL1 and VA1) have been identified in humans with diarrhea (Finkbeiner et al, 2008;2009a;2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Several reports showed that astroviruses are present worldwide and represent the second most important cause of gastroenteritis in children, after rotaviruses (Herrmann et al, 1991;Matsui et al, 2001;Moser and Schultz-Cherry 2005;De Benedictis et al, 2011). Astroviruses have also been identified in several animal species, such as cats, swine, sheep, minks, cheetahs, sea lions, bottlenose dolphins, red deer, dogs, rodents and bats (Woode and Bridger, 1978;Snodgrass et al, 1979;Gray et al, 1980;Williams, 1980;Tzipori et al, 1981;Bridger et al, 1984;Shirai et al, 1985;Woode et al, 1985;Harbour et al, 1987;Marshall et al, 1987;Vieler and Herbst, 1995;Englund et al, 2002;Lukashov and Goudsmit, 2002;Zhu et al, 2009;Blomström et al, 2010;Chu et al, 2010;Reuter et al, 2011;Tse et al, 2011). Recently, new astroviruses (MBL1 and VA1) have been identified in humans with diarrhea (Finkbeiner et al, 2008;2009a;2009b).…”
Section: Introductionmentioning
confidence: 99%
“…FRV infection was first identified by serology in cats in 1978 (19). Experimental infections have given inconsistent results, with some showing an association between rotavirus and reduced fecal quality (increased water content and suboptimal stool conformation) in kittens (8), while others failed to link infection with disease (9,10,20). Currently, rotavirus is considered to play a minor role in clinical disease and is not routinely screened for in diarrheic cases in small-animal veterinary practices (21).…”
mentioning
confidence: 99%
“…Although infections with feline rotaviruses (FRVs) rarely cause severe illness in cats (8)(9)(10)(11), FRVs have captured attention as perpetuating, albeit infrequent, sources of human disease. Human RVAs with genetic homology to feline RVAs have been isolated from widespread geographical locations, including Japan (12,13), Israel (14,15), Tunisia (16), and the United States (17).…”
mentioning
confidence: 99%
“…8 Subsequent EM-based investigations demonstrated that FAstV may be common in the stool of cats with and without diarrhea. 14,21 Experimental infection with a FAstV strain in specific pathogen-free (SPF) kittens induced enteritis and viral excretion for several days. 7 However, FAstV is not included in the diagnostic algorithms of feline enteric diseases, and its role as a primary pathogen or synergistic agent remains unclear.…”
mentioning
confidence: 99%